Maleachi, ein Ausleger des Hosea?: Hosea und Maleachi als literarischer Rahmen des Zwölfprophetenbuches - Kató, Szabolcs-Ferencz (Biblische Zeitschrift, 2025)
In theories that argue for an original, coherent corpus of the Twelve Minor Prophets, the book of Hosea plays an ambiguous role. While some studies view Hosea as a relative latecomer in the collection, others consider it as an introduction to the Twelve. After briefly presenting the main literary links proposed in the scholarly literature to Malachi, this paper reevaluates them and argues that Hosea and Malachi were shaped as a literary frame around the Twelve. In this redactional process, mainly two passages of Malachi (2:11–16; 3:19–20 MT) were inspired and consciously edited based on Hosea. Malachi employs themes, catchwords, and motifs from Hosea in these passages to adeptly address the theological issues initially raised by Hosea and further expounded upon in other works within the Twelve, ultimately arriving at a satisfying conclusion.